Systemic tumor‐targeted sodium iodide symporter (NIS) gene therapy of hepatocellular carcinoma mediated by B6 peptide polyplexes. (May 2017) - Urnauer, Sarah; Klutz, Kathrin; Grünwald, Geoffrey K.; Morys, Stephan; Schwenk, Nathalie; Zach, Christian; Gildehaus, Franz‐Josef; Rödl, Wolfgang; Ogris, Manfred; Wagner, Ernst; Spitzweg, Christine
Abstract: Background: Nonviral polymer‐based gene transfer represents an adaptable system for tumor‐targeted gene therapy because various design strategies of shuttle systems, together with the mechanistic concept of active tumor targeting, lead to improved gene delivery vectors resulting in higher tumor specificity, efficacy and safety. Methods: Using the sodium iodide symporter (NIS) as a theranostic gene, nonviral gene delivery vehicles based on linear polyethylenimine (LPEI), polyethylene glycol (PEG) and coupled to the synthetic peptide B6 (LPEI‐PEG‐B6), which specifically binds to tumor cells, were investigated in a hepatocellular carcinoma xenograft model for tumor selectivity and transduction efficiency. Results: In vitro incubation of three different tumor cell lines with LPEI‐PEG‐B6/NIS resulted in significant increase in iodide uptake activity compared to untargeted and empty vectors. After establishment of subcutaneous HuH7 tumors, NIS‐conjugated nanoparticles were injected intravenously followed by analysis of radioiodide biodistribution using 123 I–scintigraphy showing significant perchlorate‐sensitive iodide accumulation in tumors of LPEI‐PEG‐B6/NIS‐treated mice (8.0 ± 1.5% ID/g 123 I; biological half‐life of 4 h). After four cycles of repetitive polyplex/ 131 I applications, a significant delay of tumor growth was observed, which was associated with markedly improved survival in the therapy group. Conclusions: These results clearly demonstrate that systemic in vivo NIS gene transfer using nanoparticle vectors coupled to B6 tumor targeting ligand is capable of inducing tumor‐specific radioiodide uptake. This promising gene therapy approach opens the exciting prospect of NIS‐mediated radionuclide therapy in metastatic cancer, together with the possibility of combining several targeting ligands to enhance selective therapeutic efficacy in a broad field of cancer types with various receptor expression profiles.